Data Privacy in Social Media: Awareness and Comfortability of Mathematical Computing Course Session I 2023/2024 Sultan Abdul Halim Mu'adzam Shah Polytechnic’s Students - Nurulhuda Binti Che Abd Rani; Binti Ayob, Fariha (Jumper: Journal of Educational Multidisciplinary Research, 2024)
The increasing integration of social media into daily lives of individuals has raised significant concerns about data privacy. As users actively engage with various platforms, the extent to which they are aware of the privacy implications and their comfort levels with the use of personal data become vital issues. This study aimed to identify social media platforms that are often used by students, their level of awareness towards social media data privacy policy and their comfortability towards data privacy by social media companies. The respondents in this study comprises of 106 male and female students. The data are analyzed descriptively by mean, frequency and percentage. The level of awareness towards social media data privacy policy is high with average mean score 3.94, WhatsApp is the often-surfed social media platform by score of 89.62% and most students were highly comfortable with how educational social media platform used their data with mean 3.85. This study proposes the necessity of a diverse approach involving education, user empowerment, and technological advancements to enhance data privacy awareness and comfort levels among students in the realm of social media and prepare to a more secure and responsible online environment for the next generation users